Socialization Of The Importance Of Continuing Higher Education And Increasing Business Interest For High School Students - Zahara Meutia; Aryani Sairun; Putri Mauliza; Sugito Sugito; Amril Amril (Abdimas Paspama, 2024)
This socialization was carried out at the Al Fattah College Foundation High School. This socialization aims to provide awareness of the importance of continuing their education to college and foster students' interest in business. This activity method consists of 3 stages, namely service planning, service implementation and evaluation. The result of this activity was that Al-Fattah Foundation High School students received information about the world of campus as well as motivation about the importance of continuing their education to college and interest in business. This activity was carried out well as seen from the enthusiasm of all participants and the smooth running of the socialization.